2013
DOI: 10.1080/07418825.2013.770546
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Modes of Probation Officer Supervision: The Triumph of the “Synthetic” Officer?

Abstract: This article considers the continued relevance of law enforcement and social worker roles to probation officer practice, a central motif in community corrections scholarship. It also considers how these traditional functions are integrated into community-oriented supervision practices, increasingly emphasized in policy circles. Using Latent Class Analysis of data from a national community corrections survey, a four-class typology of probation officers was developed, based on their supervision practices. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 31 publications
2
72
0
Order By: Relevance
“…As individual efforts tend to emphasize and align with overarching agency objectives specific to the type of program and local context cf. Brown, 2007, p. 12), officers and departments are likely to experience drift, role conflict (Allard, Wortley, & Stewart, 2003;Moran & Lindner, 1985), or function "synthetically" (Klockars, 1972;Miller, 2015) when working with different types of technologies and offenders requires a mix of discourses or "styles" . For example, officers capable of pursuing a traditional casework approach may find their program is not amenable to such if they are tasked primarily with rule enforcement (cf.…”
Section: Penological Driftmentioning
confidence: 96%
“…As individual efforts tend to emphasize and align with overarching agency objectives specific to the type of program and local context cf. Brown, 2007, p. 12), officers and departments are likely to experience drift, role conflict (Allard, Wortley, & Stewart, 2003;Moran & Lindner, 1985), or function "synthetically" (Klockars, 1972;Miller, 2015) when working with different types of technologies and offenders requires a mix of discourses or "styles" . For example, officers capable of pursuing a traditional casework approach may find their program is not amenable to such if they are tasked primarily with rule enforcement (cf.…”
Section: Penological Driftmentioning
confidence: 96%
“…Much attention has been given to characterizing personnel dichotomously, highlighting their endorsement of treatment versus punishment orientations, such that actors in the justice system are assumed to behave as either "social workers" or "rule enforcers" in their supervision of youth in the system (Schwalbe, 2012). Research findings indicate, however, that treatment and punishment orientations are neither mutually exclusive nor inflexible as they relate to justice system personnel, nor do practices aligning with either extreme consistently predict youth outcomes (Miller, 2015). These findings have required a re-characterization of typical probation practice.…”
Section: Probation Strategiesmentioning
confidence: 78%
“…These findings have required a re-characterization of typical probation practice. Research now shows that JPOs more often meet the description of "synthetic officer" by blending elements of both care and control orientations into their work with offenders (Miller, 2015;Ward & Kupchik, 2008). For example, Schwalbe and Maschi (2009) reported that JPOs use a wide range of strategies, including those that reflect both deterrence and counseling orientations, in their interactions with youth probationers.…”
Section: Probation Strategiesmentioning
confidence: 99%
“…According to Peters (2011), the role of the juvenile probation officer is no longer a dichotomous function but rather a convergence or a blend of rehabilitation-oriented and law enforcement-oriented tasks. In this context, probation officers function as "synthetic" officers (see Miller, 2015) or "boundary spanners" (see Lutze, 2014) somewhere between social workers (e.g., care) and peace officers (e.g., control) in managing diverse cases. Depending on the circumstances, probation officers employ fluid treatment and surveillance strategies to identify individual needs and to manage each individual's risk.…”
Section: Reintegration and The Case Management Modelmentioning
confidence: 99%